Analysis of Strategic Public Financial Management Reforms on Effective Service Delivery - Chol Gabriel Majer; Lazaro Juma Anyor Makuac (International Journal of Business and Social Science Research, 2023)
The overall objective of the study is to analyze the influence of strategic public financial management changes on efficient service delivery, the best metric to use to assess how well the government provides services. To ensure economic growth and development by maximizing the efficient use of scarce public resources, the emerging country PFM reform its wasteful public finance PFM's reforms must prove successful in transparency, accountability, and reporting standards on the usage of public funds to deliver services. Both approaches focused on carefully addressing serious weaknesses in financial control and were demanding in their approach. Establishing effective control was the task, and improving control efficiency is second-order work. Improvements to the current free balance systems, the allocation and prompt payment of operations to spending agencies, the focus on monthly salaries, revenue collection monitoring verification analysis and reporting, budget control, and accounts, reporting, are some of the Public Financial Management reforms that have been put into place. The sequencing, acquisition, and disbursement of funds are all subject to stringent manual controls in public finance. The Central Payment System procurement bill and cash budget disbursement are the focus of the South Sudan PFM Reform Activities, which are information technology-driven and install new, protected, discipline and procedure-driven IFMIS information technology techniques. This study used a sample size of 47 respondents for the Ministry of Finance and Planning due to the small and easily accessible population. This study employed a questionnaire with a Likert scale to collect data. Frequency analysis and descriptive statistics were employed in the study to analyze the data acquired. The analysis was conducted with the aid of the social science statistical program SPSS, and graphs and tables were used to display the findings. Yet, the results revealed that strategic public financial management improvements and accounting methods had little impact on how well the general public was treated. The results also demonstrated that budgeting, stakeholder participation, and regulatory regulations had a favorable impact on service delivery. To prevent going over budget, government institutions should first develop plans and budgets with a high level of public involvement and ownership. The management of the institution should use technology, such as IFMIS, to improve the efficiency, transparency, and accountability of revenue collecting.